Automatic dock-to-dock control system for surface vessels using bumpless transfer. (15th January 2023) - Walmsness, Jens Emil; Helgesen, Håkon Hagen; Larsen, Stefan; Kufoalor, Giorgio Kwame Minde; Johansen, Tor Arne
Abstract: This paper proposes and demonstrates an automatic steering system designed for passenger ferries with dock-to-dock capabilities. The method consists of a modular control architecture and bumpless transfer transition strategies that enable the implementation of different independent controllers for different vessel operational phases. The method is expressed as a state machine and divides the ferry operations into three different phases, undocking, transit, and docking . The proposed modular architecture allows the use of well-proven vessel control methods such as dynamic positioning for navigating within the marine harbor environment, and a speed- and course controller for transit between the different docks. Bumpless transfer is achieved by resetting the integrator of the receiving controller, to avoid discontinuities in the control action. Specifically, the output of two controllers are constrained to be equal at the time of transition, and the integrator state value required by the receiving controller is solved. The proposed method has been demonstrated in several simulations, taking the vessel from one dock to another in a satisfactory manner. Highlights: A ship dock-to-dock control architecture using independent controllers is presented. Bumpless transfer (BT) functionality is implemented for controller transitions. A complete dock-to-dock scenario is investigated through simulation experiments. BT seamlessly combines independent controllers, enabling a flexible architecture. Stability and efficiency are improved for the transitions between control regimes.